Clinical laboratory assessment of the abuse liability of an electronic cigarette - Vansickel, Andrea R.; Weaver, Michael F.; Eissenberg, Thomas (Addiction (Abingdon, England), 2012)
ABSTRACT Aims  To provide an initial abuse liability assessment of an electronic cigarette (EC) in current tobacco cigarette smokers. Design  The first of four within‐subject sessions was an EC sampling session that involved six, 10‐puff bouts (30 seconds inter‐puff interval), each bout separated by 30 minutes. In the remaining three sessions participants made choices between 10 EC puffs and varying amounts of money, 10 EC puffs and a varying number of own brand cigarette (OB) puffs, or 10 OB puffs and varying amounts of money using the multiple‐choice procedure (MCP). The MCP was completed six times at 30‐minute intervals, and one choice was reinforced randomly at each trial. Setting  Clinical laboratory. Participants  Twenty current tobacco cigarette smokers. Measurements  Sampling session outcome measures included plasma nicotine, cardiovascular response and subjective effects. Choice session outcome was the cross‐over value on the MCP. Findings  EC use resulted in significant nicotine delivery, tobacco abstinence symptom suppression and increased product acceptability ratings. On the MCP, participants chose to receive 10 EC puffs over an average of $1.06 or three OB puffs and chose 10 OB puffs over an average of $1.50 (P < 0.003). Conclusions   Electronic cigarettes can deliver clinically significant amounts of nicotine and reduce cigarette abstinence symptoms and appear to have lower potential for abuse relative to traditional tobacco cigarettes, at least under certain laboratory conditions.